2014
DOI: 10.22329/il.v34i4.4141
|View full text |Cite
|
Sign up to set email alerts
|

Critique of the Watson-Glaser Critical Thinking Appraisal Test: The More You Know, the Lower Your Score

Abstract: Abstract:The Watson-Glaser Critical Thinking Appraisal Test is one of the oldest, most frequently used, multiple-choice criticalthinking tests on the market in business, government, and legal settings for purposes of hiring and promotion. I demonstrate, however, that the test has serious constructvalidity issues, stemming primarily from its ambiguous, unclear, misleading, and sometimes mysterious instructions. Erroneously scored items further diminish the test's validity. As a result, having enhanced knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Pemilihan pakar tersebut mungkin saja kurang tepat karena belum tentu mengusai bidang berpikir kritis dengan baik. Artinya, terjadi kesalahan dalam menentukan Subject Matter Experts di bidang berpikir kritis (Possin, 2014).…”
Section: Gambar 5 Icc Subtesunclassified
“…Pemilihan pakar tersebut mungkin saja kurang tepat karena belum tentu mengusai bidang berpikir kritis dengan baik. Artinya, terjadi kesalahan dalam menentukan Subject Matter Experts di bidang berpikir kritis (Possin, 2014).…”
Section: Gambar 5 Icc Subtesunclassified
“…Ghanizadeh (2016) found that the interaction between CT and reflective thinking contributed to students' academic achievement. While these findings are interesting, it should be noted that students' CT skills were measured using the Watson-Glaser Critical Thinking Appraisal which has been criticised for its low validity (Possin 2014). The Watson-Glaser Critical Thinking Appraisal is a multiple-choice test.…”
Section: Teaching Thinking Skills In Efl Educationmentioning
confidence: 92%
“…Critical thinking refers to reflective and rational thinking that determines an individual's beliefs or actions and shapes one's thoughts and knowledge based on his/her experiences and observations [12]. Critical thinking disposition refers to the tendency toward this thinking, and the motive or desire of critical thinking is problem solving and decision-making [13].…”
Section: Introductionmentioning
confidence: 99%